CHILDREN’S SOCIAL RELATIONSHIP OUTSIDE OF MARRIAGE BASED ON ISLAMIC LAW PERSPECTIVE IN POSO DISTRICT - Siti Fitriani AT. Israel; Nasaruddin Nasaruddin; Adam Adam (Risalah, Jurnal Pendidikan dan Studi Islam, 2022)
This paper aims to describe children’s social relationship out of marriage based on Islamic law perspective in poso district. The reseach was qualitative approach with the case study. Equality and the difference about the children right protection out of wedlock is the similarity in Islamic law and constitutional law that children out of wedlock have rights from their parents, namely the rights of parental authority, the right to care for and education of children, the right to inherit, and the right to a family name, while the difference lies in the relationship Islamic law argues that children out of wedlock have a civil relationship with their mother and their mother's family, and Constitutional Law argues that children out of wedlock have a civil relationship with their mother and mother's family, and their biological father which can be proven by evidence according to applicable law.